Fabrication of thin 140, 142Ce target foils for study of nuclear reaction dynamics. (June 2021) - Biswas, Rohan; S.R., Abhilash; Gupta, Himanshi; Umapathy, G.R.; Dawar, Anit; Nath, S.
Abstract: We report fabrication of thin target foils of 140, 142 Ce by the physical vapour deposition technique. The targets are to be used in the study of nuclear reaction dynamics with heavy ion beams. Owing to the highly reactive nature of cerium, the thin films can be oxidized during fabrication. The films were sandwiched between thin layers of nat C to impart structural stability and prevent degradation over long periods of time. The parameters for vapour deposition were frozen after several trials with natural cerium. To obtain surface morphology, elemental composition, chemical composition and thickness of the prepared targets, those were characterized using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffractometry (XRD) and Rutherford Back-scattering Spectroscopy (RBS). The thickness of the isotopic targets was in the range of 100–200  μ g /cm 2 . XRD and RBS spectra were used to determine the stoichiometry of oxide present in the films. They were observed to be in the form of CeO 2 . The isotopic composition of one of the targets was determined in an in-beam experiment using a recoil mass spectrometer. Results from the experiment matched quite well with the data provided by the supplier of the isotopic material. Highlights: Isotopically enriched films of  140, 142 Ce fabricated by physical vapour deposition. Oxide (CeO2 ) formed during deposition; confirmed by X-Ray Diffractometry. Thickness (100-200 μ g /cm 2 ) estimated by Rutherford Back-scattering Spectroscopy. Barring oxygen and carbon, no elemental impurities found in the foils. Isotopic composition of  142 Ce target foil determined in an in-beam experiment.